STRATEGIES TO STRENGTHEN FOOD SECURITY AMID THE COVID-19 PANDEMIC THROUGH TRAINING BUDIKDAMBER AND AQUAPONICS IN KEDUNG SOKA VILLAGE, PULO AMPEL SUBDISTRICT, SERANG REGENCY - Erlangga, Erlangga; Yudistira, Andrian; Maulana, Asroful; Maulida, Aulia; Sabrawijaya, Sabrawijaya (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2024)
COVID-19, which was declared  a  pandemic globally by WHO, is one    of  the  family of viruses that  attack  humans,  namely  attacking the human respiratory  tract.  In  March,  Indonesia  was  horrified by COVID-19. Therefore,    the  Indonesian  government imposed  rules  for the community to implement  Work  From  Home  (WFH) which  is  part of the Enactment of Restrictions on Community Activities  (PPKM)  to  reduce  the  increasing  growth  rate COVID-19 cases.   The impact   of  this  policy is that  it  can  cause  a  food crisis.  One of    the efforts  that  can be  done  to  prevent  the occurrence of  food  crisis  is    budikdamber  (fishcultivation   in  ember) and  aquaponics  with the discovery  of  agricultural  and  fishery  techniques that are as  healthy as budikdamber  and  aquaponics  are expected to    help  face  the current  problems.  This activity    has  many  benefits,  including the  fulfillment of    household  needs  and improving the  family economy.  People who  succeed  with  bukdidamber  techniques can create  business  opportunities  and  increase the development amid the  COVID-19  pandemic as it is now. After conducting  Budikdamber   (FishCultivation   in  Ember) and  Aquaponics  activities  in  Kedung  Soka Village,  Pulo  Ampel Subdistrict,  Serang  Regency, which  was carried out  by  KKM Bina Bangsa  Group  35  Participants in Kedung  Soka Village,  the  Kedung  Soka  community was very  enthusiastic  to  participate in the training of Making Catfish  Cultivation  in Ember. Through the  training,    the community  got new skills.   related to  overcoming  the  economic   crisis caused  by  the Covid-19 Pandemic